An Introduction to the Potential for Mobile eHealth Revolution to Impact on Hard to Reach, Marginalised and Excluded Groups - Charles Musselwhite (Mobile e-Health, 2017)
eHealth is the use of technology to serve and promote health and wellbeing needs of a population. Mobile health is the use of wireless technologies to connect, communicate and promote this amongst different stakeholders within the population. This has great potential for improving the lives of all populations, especially those from traditionally marginalised or hard-to-reach groups, including those from developing countries, older people and those with chronic conditions for example. Mobile ehealth (mhealth) can link together healthcare practitioners and individuals better, provide information or offer feedback to improve self-awareness and manage health conditions individually and can offer gems or challenges to encourage or motivate individuals to improve health. There are still concerns, however, that need addressing before mhealth can meet its potential, including, for example, security and privacy, information overload, emphasis on solving health issues rather than maintaining good health and not fully understanding how it fits into everyday lives of people, especially those not traditionally associated with technology such as older people. More research is needed on acceptability of such systems and developing standards and design and usability guidance. Overall mhealth can be seen as both enablers and disrupters, with the potential to revolutionise interactions people have about their own health but there is a need to reflect on the human and social issues surrounding such technology.